Economic evaluation of advanced practice physiotherapy models of care: a systematic review with meta-analyses - Simon Lafrance; Anthony Demont; Kednapa Thavorn; Julio Fernandes; Carlo Santaguida; François Desmeules (BMC, 2021)
Abstract Background The objective of this systematic review is to appraise evidence on the economic evaluations of advanced practice physiotherapy (APP) care compared to usual medical care. Methods Systematic searches were conducted up to September 2021 in selected electronic bibliographical databases. Economic evaluation studies on an APP model of care were included. Economic data such as health care costs, patient costs, productivity losses were extracted. Methodological quality of included studies was assessed with the Effective Public Health Practice Project tool and the Critical Appraisal Skills Programme checklist. Meta-analyses were performed and mean differences (MD) in costs per patient were calculated using random-effect inverse variance models. Certainty of the evidence was assessed with the GRADE Approach. Results Twelve studies (n = 14,649 participants) including four randomized controlled trials, seven analytical cohort studies and one economic modeling study were included. The clinical settings of APP models of care included primary, emergency and specialized secondary care such as orthopaedics, paediatrics and gynaecology. The majority of the included participants were adults with musculoskeletal disorders (n = 12,915). Based on low quality evidence, health system costs including salaries, diagnostic tests, medications, and follow-up visits were significantly lower with APP care than with usual medical care, at 2 to 12-month follow-up (MD: − 145.02 €/patient; 95%CI: − 251.89 to − 38.14; n = 7648). Based on low quality evidence, patient costs including travel and paid medication prescriptions, or treatments were significantly higher with APP care compared to usual medical care, at 2 to 6-month follow-up (MD: 22.18 €/patient; 95%CI: 0.40 to 43.96; n = 1485). Based on very low quality evidence, no significant differences in productivity losses per patient were reported between both types of care (MD: 450 €/patient; 95%CI: − 80 to 970; n = 819). Conclusions This is the first systematic review and meta-analysis on the economic evaluation of APP models of care. Low quality evidence suggests that APP care might result in lower health care costs, but higher patient costs compared to usual medical care. Costs differences may vary depending on various factors such as the cost methodology used and on the clinical setting. More evidence is needed to evaluate cost benefits of APP models of care.